Thoracic Splenosis: The Luckiest Nodule You Can Have - Mello Vieira, Marta; Barbosa, Sara; Morais, Mariana; Soares, Leonor; Fevereiro, Maria do Carmo (International Journal of Innovative Research in Medical Science, 2025)
Thoracic splenosis is characterised by the autotransplantation of splenic tissue into the thoracic cavity, following splenic and diaphragmatic rupture. It is usually asymptomatic and diagnosed incidentally. The authors present the case of a 61-year-old woman, with a history of a car accident 36 years prior which resulted in splenectomy. The patient presented to the emergency department with a syncytial respiratory virus infection, which led to the identification on computed tomography of extensive nodular thickening of the left peripheric pleura (11cm extension, 2,9cm thickness), suggestive of neoplasia. She underwent a percutaneous pleural biopsy, followed by video-assisted thoracoscopy, which revealed lymphoid tissue with germinal centres and abundant lipid-laden CD68+ macrophages. A positron emission tomography with 18F-FDG identified a low metabolic signal on the left pleura. Follow-up chest computed tomography demonstrated the stability of the nodular lesions. After a multi-disciplinary discussion, given the patient's medical history, the hypothesis of thoracic splenosis was considered the most likely diagnosis. This case brings our attention to this rare entity, highlighting the importance of a detailed clinical history, a persistent search for a diagnosis and a multi-disciplinary approach.